THE USE OF SOCIAL MEDIA IN GENRE-BASED APPROACH : A Case Study to Teach Argumentative Writing and Critical Thinking - Kuswanto, Indriani (2015)
This case study aims to investigate the use of social media in genre-based approach. Three data collection triangulation techniques were used in this study, i.e. the documentation of students' argumentative writings, observation and interview. The data were the analyzed using the theory of Genre-Based Approach (GBA), Critical Thinking (CT), Argumentative Writing, and The Use of Social Media in Tertiary Education. In addition, to show the effect of social media in genre-based approach, the students' writings were analyzed using Systemic Functional Grammar (SFG). The results of the present study revealed two findings related to the research questions. First, when used appropriately in GBA, social media is proven to be helpful in developing the students' argumentative writing and critical thinking. Social media exposes students to lots of information online and when immersed in GBA, it was confirmed that the students' argumentative writing significantly improved. Second, the interview data uncovered that although familiar with the concepts of critical thinking, Indonesian students still believe themselves as uncritical thinkers. This is due to the social factor such as the authoritarian society which demands them to remain uncritical. Moreover, the interview data unfolded that students perceived social media as a helpful learning tool to build arguments in their writings. The findings above suggest that using social media in GBA to develop students' argumentative writing and critical thinking by techno-literate teachers is worth trying to create more effective teaching and learning activities. Keywords: social media, genre-based approach, argumentative writing, critical thinking, systemic functional grammar